The Effect of Mobile Banking Application on Customer Interaction in the Jordanian Banking Industry - Aldiabat, Khaled; Al-Gasaymeh, Anwar; K.Rashid, Ameer Sardar (International Journal of Interactive Mobile Technologies (iJIM), 2019)
Banks have changed from paper-based banking solutions provider to the latest of the technologies like mobile banking. Adoption of mobile-banking has received more attention in recent years, because there are more phones than computers in the market. But, like in any emerging technology, there exist barriers to the adoption of mobile banking services. This study will attempt to technically address these largely unfounded factors while helping to lay a roadmap for proper implementation of mobile banking technology in the Jordanian banking industry. The study found that Supportive Access factor of mobile banking is associated with the user satisfaction related to mobile banking.